Poster 195: Inverse Relationship of Hip Capsular Thickness on Magentic Resonance Imaging and Increased Axial Distraction Under Anesthesia: Further Characterization of Hip Laxity. Issue 7 (30th July 2022) - Featherall, Joseph; Froerer, Devin; Mortensen, Alexander; Aoki, Stephen; Metz, Allan
Objectives: The hip joint derives its stability from several biomechanical and anatomic factors, including the ligaments of the hip capsule. Recent research has implicated the hip capsule in the pathogenesis of hip instability, which is especially important when considering the inherent violation of the hip capsule with arthroscopic procedures. The purpose of this study was to characterize the relationship between quantitative axial hip distraction and capsular thickness on magnetic resonance imaging (MRI). We hypothesized that thinner hip capsules would be associated with increased axial distraction distances at maximal traction force. Methods: A retrospective review of the senior author's primary hip arthroscopic procedures was conducted from November 2018 to June 2021. Inclusion criteria were 1) diagnosis of FAI, 2) pre-operative MRI, 3) and intra-operative fluoroscopic imaging conducted at 0 and 100 pounds (lbs) of axial distraction. Intra-operative, fluoroscopic images were obtained at the beginning of the procedure prior to any instrumentation at 0 lbs and 100 lbs of axial traction force. Distraction distance was calculated by comparing the difference of the initial joint space to the total joint space at 100 lbs and measured using a picture archiving and communication system (PACS). Hip capsule thickness was measured on pre-operative MRI or MRA imaging. Anterior and posterior capsular thickness was measured in the axial plane, while superior and inferior capsule thickness was measured in the coronal plane. Anterior and superior measurements approximated the iliofemoral ligament, with posterior and inferior measurements approximating the ischiofemoral and pubofemoral ligaments. Three measurements were taken in each region of the hip capsule and averaged to produce an accurate estimate of hip capsule thickness in each region. Statistical analysis was conducted using multiple linear regression and independent samples t-tests with an alpha of <0.05. Results: Eighty patients were included from 121 charts reviewed, with 41 patients being excluded for lack of appropriate preoperative imaging to evaluate joint distraction or capsular thickness. Bivariable regression demonstrated increased distraction associated with female sex (B = -4.303, p <0.001). Axial distraction was also shown to be increased in relation to decreased capsular thickness in the anterior axial (B = -1.291, p < 0.001), superior coronal (B = -1.433, p <0.001), and posterior axial regions (B = -1.293, p = 0.028). Multivariable regression of the hip capsular measurements demonstrated increased axial distraction associated with decreased superior coronal capsular thickness (B = -1.402, p < 0.001). Independent samples t-tests showed females had significantly decreased hip capsular thickness in the superior coronal, anterior axial, and posterior axial regions (p = <0.05). Conclusions: Our results show several significant associations with hip capsular thickness and hip axial distraction. Patients with thinner hip capsules in the anterior axial, posterior axial, and superior coronal regions were found to have increased axial distraction distances at 100 lbs of force. These findings are in line with previous descriptions of the importance of the iliofemoral ligament and hip stability, which was approximated in this study using the anterior axial and superior coronal measurements. While female sex was observed to be associated with increased axial distraction, this may potentially be secondary to females having statistically thinner hip capsules as shown by our findings. This observation provides a more nuanced anatomic explanation for this association that has been previously reported regarding patient sex and hip laxity. Our findings further demonstrate the importance of the hip capsule as it pertains to hip joint stability, providing a quantitative method to evaluate hip capsular thickness and joint distraction. Clinically, these results are important to consider in the evaluation of hip instability and capsular insufficiency. Table 1. Multivariable regression results with axial distraction at 100 1bs of force as the independent variable